1979
DOI: 10.1148/130.1.223
|View full text |Cite
|
Sign up to set email alerts
|

Thallium-201: Quantitation of Right Ventricular Hypertrophy in Chronically Hypoxic Rats

Abstract: Sprague Dawley rats were divided into two groups. Ten were kept in room air and 10 in hypobaric hypoxia (air at 380 mm Hg). After two weeks all were injected intravenously with 50 muCi of 201Tl and sacrificed. The right and left ventricles were separated, weighed, and measured for radioactivity in a gamma well counter. Left and right ventricular mass ratios (MR) correlated with 201Tl radioactivity ratios (TAR) in both control and hypoxic rats: r = 0.962 where MR = 0.863 TAR + 0.27. Myocardial 201Tl uptake refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Chronic hypoxia is a model of group 3 PH (although it is often incorrectly extrapolated to represent group 1 PH). Exposure of rodents that are not native to high altitude to moderate hypoxia elevates PVR and PAP and causes RVH (94). Interestingly, in models of chronic hypoxia, acute hypoxic pulmonary vasoconstriction is impaired (95).…”
Section: Chronic Hypoxic Pulmonary Hypertensionmentioning
confidence: 99%
“…Chronic hypoxia is a model of group 3 PH (although it is often incorrectly extrapolated to represent group 1 PH). Exposure of rodents that are not native to high altitude to moderate hypoxia elevates PVR and PAP and causes RVH (94). Interestingly, in models of chronic hypoxia, acute hypoxic pulmonary vasoconstriction is impaired (95).…”
Section: Chronic Hypoxic Pulmonary Hypertensionmentioning
confidence: 99%
“…These results indicate that chronic hypoxia induces modulations of AT1 and AT2 receptors in both cardiac ventricles probably through direct and indirect mechanisms, respectively, which modulations may participate in myogenic (at the level of smooth or striated myocytes) rather than in the growth response of the heart to hypoxia. chronic hypoxia; heart ventricles; angiotensin II; AT1 and AT 2 receptor subtypes CHRONIC HYPOXIA-INDUCED pulmonary hypertension is characterized by an increased pulmonary vascular resistance due to pulmonary artery thickening that impedes ejection of blood by the cardiac right ventricle (RV) and leads to RV hypertrophy (1,20,21,33). Evidence that chronic hypoxia increases the plasma levels of renin (9), angiotensin-converting enzyme (ACE) (24), and angiotensin II (ANG II) (42) has stimulated interest in the contribution of the renin-angiotensin system to the hypoxia-induced cardiopulmonary changes.…”
mentioning
confidence: 99%
“…Strauss et al (1975) demonstrated that its concentration in the dog myocardium was 2.08% dose/organ at 10 min after administration and 1.34% at 20 min. Rabinovitch et al (1979) also described the concentration in the heart of rats was 3% at 10 min after administration. Myocardial uptake of it in our PBS control rabbits was 2.6% dose/organ, similar to the results of Rabinovitch et al Rabinovitch et al (1979) showed that, in their experimental right ventricular hypertrophy of hypoxic rats, the increase in right ventricular mass was proportional to the increase in thallium-201 uptake.…”
Section: Resultsmentioning
confidence: 93%
“…Rabinovitch et al (1979) also described the concentration in the heart of rats was 3% at 10 min after administration. Myocardial uptake of it in our PBS control rabbits was 2.6% dose/organ, similar to the results of Rabinovitch et al Rabinovitch et al (1979) showed that, in their experimental right ventricular hypertrophy of hypoxic rats, the increase in right ventricular mass was proportional to the increase in thallium-201 uptake. However, in our experiments, increase in right ventricular weight of the embolic rabbits was not always proportional to increase in the uptake of thallium in it.…”
Section: Resultsmentioning
confidence: 93%